2017
DOI: 10.1016/j.jpowsour.2017.03.121
|View full text |Cite
|
Sign up to set email alerts
|

Phase change effect on the structural and electrochemical behaviour of pure and doped vanadium pentoxide as positive electrodes for lithium ion batteries

Abstract: Electrospun ceramic oxide fibers find myriad uses as energy materials such as in battery electrodes and vanadium oxides are one such family of materials. In this study, the structural and energy storage properties of electrospun vanadium pentoxide are compared to approximately 10 at% barium and titanium-doped equivalents. The vanadium pentoxide was doped in order to improve its electrochemical performance. The materials are characterised using powder X-ray diffraction, scanning electron microscopy, energy disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…In the meantime, the fast Li transport can occur along the a – b plane because of fast lithium ion diffusion channels with lower energy barriers. V 2 O 5 is regarded as a promising candidate electrode material for lithium-ion batteries. …”
mentioning
confidence: 99%
“…In the meantime, the fast Li transport can occur along the a – b plane because of fast lithium ion diffusion channels with lower energy barriers. V 2 O 5 is regarded as a promising candidate electrode material for lithium-ion batteries. …”
mentioning
confidence: 99%
“…In addition to Mg 20,80 it is claimed that Zn 81 and Ca 20 can be electrochemically inserted into V 2 O 5 , and are thus of interest to examine. Ba 44 and Fe 46,47,82 have been used as dopants in the V 2 O 5 system for Li-ion batteries in the literature. Be and Cd are not of experimental interest as dopants or intercalants due to their toxicity, but were selected to give additional data points to demonstrate the stability-radius trend.…”
Section: Relative Stability Of M-incorporated α and δ -V 2 Omentioning
confidence: 99%
“…A previous study described the phase change effects of electrospun V2O5 doped with ca. 10 at% redox inactive dopants, Ba 2+ or Ti 4+ [23]. It was found that the cycle stability of the doped V2O5 was improved compared to undoped V2O5 in both cases, and additionally that the Ti 4+ dopant resulted in increased charge storage capacity.…”
Section: Introductionmentioning
confidence: 97%
“…The process is flexible and could also allow incorporation of carbon derivatives into the electrospun fibres [36]. Electrospun undoped V2O5 has been synthesised and investigated by several groups for energy storage purposes [21][22][23][24][25]. Determining the location of dopants is challenging experimentally and we have used computational atomistic simulation techniques to investigate the energetics for substitutional and interstitial Na + , Ba 2+ and Al 3+ ions, to determine their likely positions in the V2O5 lattice and help rationalize the electronic conductivity and electrochemical behavior of the doped systems observed experimentally.…”
Section: Introductionmentioning
confidence: 99%